Epidemiologia das infecções de sítio cirúrgico em mulheres submetidas a cesariana em um hospital terciário do município de Uberlândia - Leonel, Ariana Aparecida Soares (2018)
Introduction: Despite the current efforts towards natural birth, the number of cesarean sections in Brazil remains as one of the highest in the world, which increases the concern at health centers regarding the complications of such procedure. One of the main concerns is the occurrence of infectious complications, since cesarean sections are known to bring higher risks of such kind. Objective: To identify the rate of occurrence of surgical infections (from cesarean sections), as well as the demographic and clinic profiles of women with such diagnosis. Material and methods: To lower the impact of sub-notifications on the ISC rate, we used the active-search tool. In this sense, the subjects were approached in person on post-surgical hospitalized stage, when pre-pregnancy, pre-birth and birth information was collected. The subjects were contacted by phone during 30 days, and the women who indicated the occurrence of ISC were considered in the sample of this study. Results and discussion: 125 subjects were followed up, and 14 presented ISC, resulting in an occurrence rate of 11.20% (n=14). The most common background factor in the subjects who developed infection was some degree of overweight and obesity, identified in 50% of the subjects (n=7). Among the pre-birth characteristics, the most commonly identified factor was hypothyroidism with 28.6% (n=4); and 35.7% (n=5) of the women presented some kind of infectious process during pregnancy. Conclusion: ISC refers to puerperal complications with variable etiology, highlighting the impact of overweight and obesity states. Also, it is crucial to follow up discharged patients to identify the actual number of occurrences of such complication.